2011
DOI: 10.1103/physrevb.83.134436
|View full text |Cite
|
Sign up to set email alerts
|

Positive antiphase boundary domain wall magnetoresistance in Fe3O4(110) heteroepitaxial films

Abstract: We observe a strong crystallographic direction dependence on the low-field magnetoresistance (MR) behavior of the epitaxial Fe 3 O 4 (110) films grown on MgO (110) substrates. The sign of MR is positive when the current and field are parallel to [001], whereas along the [110] direction its sign is negative, similarly to that commonly observed for (100) oriented Fe 3 O 4 films. We relate this effect to the presence of antiphase boundaries (APB) and subsequent reduction in the width of canted spin structure in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
47
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 44 publications
(78 reference statements)
3
47
2
Order By: Relevance
“…Characteristic steps are observed in the hysteresis loops around zero field. These step-like features are commonly found in CFO thin films [54,60] and other ferrimagnetic oxides such as Fe 3 O 4 [57] or -Fe 2 O 3 [61], and have been attributed to the result of coupled antiferromagnetic domains due to the presence of APBs by Sofin et al [62]. A larger density of APBs would lead to a larger step at zero field.…”
Section: Iiic Comparison Between Vsm and Smr Measurementsmentioning
confidence: 77%
See 1 more Smart Citation
“…Characteristic steps are observed in the hysteresis loops around zero field. These step-like features are commonly found in CFO thin films [54,60] and other ferrimagnetic oxides such as Fe 3 O 4 [57] or -Fe 2 O 3 [61], and have been attributed to the result of coupled antiferromagnetic domains due to the presence of APBs by Sofin et al [62]. A larger density of APBs would lead to a larger step at zero field.…”
Section: Iiic Comparison Between Vsm and Smr Measurementsmentioning
confidence: 77%
“…Elastic energy shall be released during film growth and the simplest way is to reduce the APBs density away from the interface with the substrate. Within the scope of APBs model developed by Sofin et al [62], the observed difference between bulk and surface magnetization (green line in Fig. 5b) would reflect the magnetization reversal of domains antiferromagnetically coupled across APBs.…”
Section: Figure 5 (A) Magnetic Hysteresis Loops For the Pt(2 Nm)/cfomentioning
confidence: 85%
“…The longer steps terminate at surface Fe tet atoms (grey), while the shorter steps terminate at the Fe oct atoms (red). (110) surface has been less studied than the (111) and (100) surfaces, both experimentally [306][307][308] and computationally [309][310][311]. In principle, there are two possibilities to truncate the bulk at the (110) [228].…”
Section: 44mentioning
confidence: 99%
“…This value is much lower than values reported for Fe 3 O 4 thin films grown on (001)-oriented MgO or Al 2 O 3 substrates. 70,71 This might be explained by the disordered growth within the initial phase of the deposition process, leading to a disconnection of the Fe 3 O 4 thin film with the surface structure of the BTO substrate. Thus, the deviation in saturation magnetization ∆M s might not be explained by APBs alone.…”
mentioning
confidence: 99%